Análisis de defectos en tubos de acero con costura - Sarrate, Mariano; De Vedia, Luis; Velo, L. (Comisión Nacional de Energía Atómica; Argentina, 1972)
Fil: Sarrate, Mariano Comisión Nacional de Energía Atómica; Argentina